Is fingerprint ridge density influenced by hand dimensions? - Sharma, Siddharatha; Krishan, Kewal; Rani, Deepika; Mukhra, Richa; Kanchan, Tanuj (Acta Biomedica Atenei Parmensis, 2022)
Background and objective: Various aspects of fingerprint resarch were extensively explored in the past. However, the correlation between fingerprint ridge density and hand dimensions has not yet been documented. Therefore, the present study has investigated the relationship so that some conclusions regarding the association can be established. Methods: The study included 500 subjects (250 males and 250 females) between the ages of 18 to 25 years who belonged to the Rajput community of the Shimla and Solan districts of Himachal Pradesh state of North India. The sexual dimorphism among the ridge count was examined using student’s t–test. The relationship of fingerprint ridge density with hand dimensions among both the sexes and pooled data was analyzed using Pearson’s correlation coefficient. Results: All the fingers on both hands showed statistically significant sex differences. When all digits were considered together, the left little finger in males and right middle finger in females showed a weak but significant correlation with hand length while all the digits when considered in combination reported strong correlation hand length measurements. Similarly, right thumb showed significant correlation with hand breadth. All the ten digits showed highly significant correlation with hand breadth when pooled data was examined. Conclusion: The ridge density correlates with the hand dimensions in the case of pooled data. This relationship can then be used to devise prediction equations for hand dimensions based on ridge density, or vice-versa for pooled data. The equations will also help in estimating hand dimensions based on ridge density and vice-versa.